PENGUATAN BRANDING JAJE GINA DI BATUBULAN GIANYAR MELALUI SOSIAL MEDIA MARKETING DAN SISTEM ADMINISTRASI SEDERHANA - I Putu Widyarsana; Putu Eny Suhardiyani; I Gusti Putu Hardi Yudana (Jurnal Pengabdian Informatika, 2026)
MSMEs (Micro, Small, and Medium Enterprises) that produce traditional snacks like Jaje Gina play a strategic role in fulfilling religious ritual needs. The name "Jaje Gina" refers to a specific type of traditional snack used as upakara or a component of banten (offerings). The success of these MSMEs is not merely an economic matter but also about preserving Balinese culture and traditions. These businesses ensure that ceremonial traditions can be performed completely according to customary requirements. Furthermore, traditional snack MSMEs have the potential to grow when combined with modern (digital) marketing strategies and the strengthening of their identity as cultural products. The community service partner is Mrs. Ni Wayan Suryani, who sells various types of jaje gina. This business has been operating for approximately 15 years, with production based at her residence on Jalan Batuyang, Gang Rajawali No. 100X, Gianyar Regency. Although this MSME holds great potential, it faces several obstacles. Business administrative records are still managed manually, making it difficult for the owner to monitor income, expenses, profit and loss, and raw material stocks. Additionally, marketing remains limited to the surrounding area and has not yet optimized digital media, despite current consumer trends where product information is primarily sought through social media and the internet. These conditions prevent the MSME from maximizing its business development. To address these challenges, a Simple Administration System based on Microsoft Excel is required—one that is user-friendly, practical, and capable of generating automatic reports. Furthermore, Digital Branding Strengthening through the use of websites and Instagram is essential so that Jaje Gina products can gain wider recognition, build a professional image, and increase competitiveness. Based on the partner's situation, the community service team provides training on administrative systems, including an introduction to Microsoft Excel, data input, and the use of automated formulas, enabling the partner to have an effective and efficient simple business administration system. In addition to administrative recording, digital branding is a key factor in enhancing MSME competitiveness. Consequently, to strengthen digital branding, the community service team provides mentoring through website creation and the management of Facebook as a digital promotion medium to expand marketing reach and improve the professional image of Jaje Gina, making it better known to both local and online consumers. The website features a product catalog, pricing, business profile, ordering contact (WhatsApp), and customer testimonials, serving as a digital storefront. Meanwhile, Instagram is utilized for visual promotion through photos, videos, and product stories, with content including product photography, manufacturing processes, sales promotions, and testimonials. The output of this community service is a scientific publication in the Jurnal Pengabdian Informatika (JUPITA). This internal community service activity is expected to assist the Jaje Gina MSME in Batubulan, Gianyar, in improving business management quality through an Excel-based administrative system and expanding marketing reach through digital branding on websites and Instagram. Ultimately, the MSME can become more professional, competitive, and contribute to the strengthening of the local economy.